The impact of the actions of Education Inspection in the current teacher training - Miguel Ángel González Ortiz (ADIDE Federación, 2016)
This article analyses the impact that a priority action on the assessment process in vocational training has had. It has been carried out by the General Education Inspection of Castilla-La Mancha throughout this school year and it is classified within the overall action and training plan for the teachers who teach this level through the Regional Centre for Teacher Training. For the analysis of this work, we took into account the degree of involvement of the teachers who teach middle and upper-grade vocational training who were enrolled in a specific course organised by the Regional Centre for Teacher Training called Didactic syllabi and assessment processes in Vocational Training. These teachers belonged to schools that offer middle and upper-grade vocational training which were supervised by education inspectors of Castilla-La Mancha.The conclusions obtained in the analysis of this work are a true reflection of the performance of education inspection in vocational training.